A medium-term follow-up of adult lumbar tuberculosis treating with 3 surgical approaches. Issue 45 (November 2017) - Zhang, Qi Hong; Guo, Qiang; Guo, Chaofeng; Wu, Jianhuang; Liu, Jinyang; Gao, Qile; Wang, Yuxiang
Abstract : Abstract: Surgical intervention is an important option for treating lumbar tuberculosis. Previous studies have reported different surgical intervention procedures. To our knowledge, few studies have compared the clinical results of mid-term follow-up of 3 different surgeries in surgical treatment of spinal tuberculosis. This study's purpose is to evaluate the effectiveness of 3 different surgeries for the treatment of lumbar tuberculosis in adult and analyze the mid-term influence of the surgery on quality of life. Between June 2004 and January 2010, a total of 137 adult patients (54 women and 83 men) with lumbar tuberculosis were recruited for this study. The patients were divided into 3 groups based on administered surgeries: posterior, anterior, and combined posterior-anterior. The trauma index (operation time, blood loss, length of hospital stay, and complications), imaging parameters (segment kyphotic angle, correction rate, loss angle, and bone fusion time), and quality-of-life indicators, including Oswestry Disability Index (ODI), the Frankel grade, visual analog scale (VAS), and Macnab score, were collected. The posterior group experienced the lowest trauma index, whereas the combined group faced the highest trauma index. The anterior group's kyphosis correction rate of (52% ± 5.45%) was significantly inferior to the posterior group (74% ± 5.04%) and the combined group (69% ± 7.95%), whereas the loss of correction in the anterior group (2.5°) was higher than the losses of correction in the posterior group (0.8°) and combined group (1.1°). The mean bone fusion times of the 3 groups were similar. Postsurgery quality of life was markedly improved in all patients. The improvement rates of the ODI, VAS, and the excellent and good rate per the Macnab score were similar among the 3 groups at the final follow-up. Based on a retrospective study, for patients with lumbar tuberculosis, use of the anterior approach should be limited. Although the combined approach produced satisfactory outcomes, it remains more traumatic. Compared with the anterior surgery and the combined surgery, the posterior-only approach is safer and less invasive.